2019
DOI: 10.3390/app9112382
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Ranging Technique Based on Optical Camera Communications and Time Difference of Arrival

Abstract: In this work, a new Time Difference of Arrival (TDoA) scheme for distance measurement based on Optical Camera Communication (OCC) systems is proposed. It relies on the use of optical pulses instead of radio-frequency signals as the time reference triggers, and the introduction of a rolling shutter camera, whose characteristics allows substituting the timer modules used in conventional TDoA techniques by image processing of the illuminated area in the picture. This processing on the camera’s images provides tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Thus, a noise-free system is considered in this work. The conventional trilateration technique based on a range of three minimum observation points offers the advantage of simple geometrical solutions [ 14 ]. Using the RSS algorithm and 4-Tx (i.e., LEDs), the for the LoS path is given as [ 33 , 34 ]: where and where K is the total number of Txs, is the light source irradiance half-power angle, and φ are the tilted irradiance angle from the k th Tx to the Rx and the receiving incident angle, respectively.…”
Section: Proposed Visible Light Positioning (Vlp) System Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a noise-free system is considered in this work. The conventional trilateration technique based on a range of three minimum observation points offers the advantage of simple geometrical solutions [ 14 ]. Using the RSS algorithm and 4-Tx (i.e., LEDs), the for the LoS path is given as [ 33 , 34 ]: where and where K is the total number of Txs, is the light source irradiance half-power angle, and φ are the tilted irradiance angle from the k th Tx to the Rx and the receiving incident angle, respectively.…”
Section: Proposed Visible Light Positioning (Vlp) System Modelmentioning
confidence: 99%
“…Most research reported on VLP has focused on the investigation of geometrical properties using triangulation/trilateration, fingerprinting, or proximity methods to determine the transmission distance based on establishing a one-to-one relationship between the target location and its received signal strength (RSS). In such works, the analyses were based on the intensity modulation, angle of arrival [ 9 ], time of arrival [ 10 ], time difference of arrival [ 14 ], time of flight (TOF), and direct detection. In VLP systems, linear least square (LLS) or non-linear least square (NLLS) algorithms are often used for the position estimation [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%